Differences in the metabolic profiles and antioxidant activities of wild and cultivated black soybeans evaluated by correlation analysis - Xu, Jiu Liang; Shin, Jeong-Sook; Park, Soo-Kwon; Kang, Sungtaeg; Jeong, Soon -Chun; Moon, Jung-Kyung; Choi, Yongsoo (ELSEVIER SCIENCE BV, 2017)
Wild soybeans are considered a potential resource for soybean domestication and an important source of genetic diversity for soybean crop improvement. Understanding metabolite-caused bioactivity differences between cultivated and wild soybeans is essential for designing a soybean with enhanced nutritional traits. In this study, the non-targeted metabolic profiling of 26 soybean varieties, 15 wild black soybeans (WBS) and 11 cultivated black soybeans (CBS), using liquid chromatography-mass spectrometry (LC-MS) in combination with multivariate analysis revealed significant differences in 25 differential metabolites. Among these, the soyasaponins Ab and Bb were found to be characteristic metabolites expressed more substantially in CBS than in WBS. Three different antioxidant assays and correlation analysis identified major and minor antioxidants that contributed to WBS having an antioxidant activity 4- to 8-fold stronger than that of CBS. Epicatechin, procyanidin B2, and cyanidin-3-O-glucoside were identified by both association analysis and the online LC-ABTS radical scavenging assay as being major antioxidants.
Keywords: MAX L. MERR.; GLYCINE-SOJA; SOY PROTEIN; SEED COAT; IDENTIFICATION; ISOFLAVONES; ANTHOCYANINS; QUANTIFICATION; BIOSYNTHESIS; SOYASAPONIN